Higher education and SDG4 : quality education - Kupe, Tawana (Higher education and the sustainable development goals, 2024)
Of all the 17 United Nations Sustainable Development Goals, SDG4 is especially and directly relevant to the work of Higher Education (HE) institutions. Adopting a future-facing view, Higher Education and SDG4 cuts through the dynamic education landscape to highlight its material contribution and actions needed to achieve 'Quality Education'. Navigating current realities and critical issues, the chapters move beyond reflection, and present ideas, approaches, and possible solutions to enable a step change contribution by HE towards achieving SDG4. Incorporating the voices and perspectives of students, faculty, and staff, the chapters consider the complex circumstances that drive inequity and what universities can do to tackle it. Calling for intentional, inclusive, and, above all, immediate action, Higher Education and SDG4 looks outside educational ecosystems to how HE institutions can build societal capabilities and become a key determinant of sustainable futures. Higher Education and the Sustainable Development Goals is a series of 17 books that address each of the SDGs through the lens of higher education. Adopting a solutions-based approach, each book focuses on how higher education is advancing delivery of Agenda 2030. The series is edited by Wendy Purcell, Professor with Rutgers University and Academic Research Scholar with Harvard University; Emeritus Professor and University President Emerita.